Advanced machine learning model for better prediction accuracy of soil temperature at different depths - Alizamir M.; Kisi O.; Ahmed A.N.; Mert C.; Fai C.M.; Kim S.; Kim N.W.; El-Shafie A. (Public Library of Science, 2023)
air temperature; article; artificial neural network; atmosphere; chemical reaction; controlled study; ecosystem; linear regression analysis; prediction; soil depth; soil temperature; solar radiation; wind speed; chemistry; ecosystem; environmental monitoring; machine learning; river; soil; statistical model; temperature; Atmosphere; Ecosystem; Environmental Monitoring; Linear Models; Machine Learning; Neural Networks, Computer; Rivers; Soil; Temperature